Autocad 2007 a Problem-Solving Approach (Paperback) (Sách photo) - Tickoo Sham (Autodesk Press, 2006)
Updated to the newest release, AutoCAD® 2007: A Problem-Solving Approach is a comprehensive resource containing detailed explanations of AutoCAD 2007 commands that enables both basic and advanced users to take maximum advantage of Autodesk®'s newest and most primary software features. Carefully organized to progress from the rudiments of AutoCAD to the important concepts of 3D modeling and, finally, customization, this book caters to the needs of beginners, as well as industry professionals.